Hypertension Management in Pre- and Post Percutaneous Coronary Intervention Patients: An Expert Opinion of Cardiologists from India - Kumar, Arram Sreenivas; Kumar, Viveka; Shah, Chetan P.; Kasturi, Sridhar; Birla, Ashish; Revankar, Santosh; Yadav, Neeraj Kumar (Journal of the Practice of Cardiovascular Sciences, 2024)
Introduction: Despite recent advancements in hypertension management, a significant portion of the population in India still has uncontrolled blood pressure (BP), particularly post percutaneous coronary intervention (PCI). This paper fulfils the gap between post-PCI and hypertension management, ensuring hypertension is well-controlled before, during, and after PCI. Methods: Cardiologists (interventional, n = 256; noninterventional, n = 336) throughout India who treated hypertensive patients, post PCI were invited to participate in a survey and virtual meetings. The perception and practices in managing these patients and strategies to improve BP control were captured. Results: Out of 593 cardiologists, 57.5% opined that heart failure (HF) was more common in patients with hypertension indicated for PCI. The target BP after PCI for patients aged <65 years and >65 years was recommended to be 121-130/80 mmHg by 39% of experts while 131-140/90 mmHg by 33.2% of experts, respectively, with a target heart rate of 60-80 bpm. Angiotensin II receptor blockers (ARBs) were considered the most effective antihypertensive agent in different comorbid conditions. Metoprolol and bisoprolol were the most preferred cardio-selective beta-blockers for both post-PCI and HF. A combination of ARBs and beta-blockers after the intervention was suggested in hypertensive patients with coronary artery disease and diabetes mellitus (57.0%), stroke (41.1%), and HF (44.9%). Conclusions: Managing BP and heart rate in patients with hypertension post-PCI is important. In monotherapy, ARBs followed by beta-blockers and angiotensin-converting enzyme inhibitors, were the most preferred antihypertensive agents in these patients with different comorbid conditions. While a combination of ARB and beta-blocker was preferred in patients with PCI and multiple comorbidities.